PENINGKATAN EKSPRESI mRNA TNF-? PADA SEL PBMC TERINFEKSI VIRUS HEPATITIS B YANG TERPAPAR EKSTRAK UBI JALAR UNGU (Ipomoea batatas L.) - Hendrayana, Made Agus (E-Jurnal Medika Udayana, 2023)
Hepatitis B Virus infection is a serious health problem throughout the world that can cause death. Purple sweet potatoes contain quite high levels of anthocyanins. Anthocyanins have been widely proven to act as immunostimulators by influencing levels of the cytokine TNF-?. This study aims to prove that purple sweet potato extract has an effect on TNF-? mRNA expression in PBMC cell cultures infected with the hepatitis B virus. The research sample was a PBMC cell culture taken from an asymptomatic chronic Hepatitis B patient. The samples from the normal saline control group were 18 wells and the treatment group with purple sweet potato extract with an anthocyanin content of 0.265 mg/100g was 18 wells. Purple sweet potato extract is made using the maceration technique. PBMCs were isolated from blood using Ficoll-Paque. PBMC cells were cultured in 24 well plates with complete RPMI 1640 medium. Examination of TNF-? mRNA expression using Relative 1-step qRT-PCR quantification. The results showed the mean difference in TNF-? mRNA expression between the treatment and control groups: 20.08 fg/µL (p<0.05), there was a significant increase in TNF-? mRNA expression. The results of this study can be concluded that administration of purple sweet potato extract in vitro can increase TNF-? mRNA expression in PBMC cultures infected with hepatitis B virus.